2019
DOI: 10.2174/1573399815666190115151500
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNA-21 and miRNA-23a Expression Signature as Potential Biomarkers for Early Detection of Non-Small-Cell Lung Cancer

Abstract: Background and Aim: Lung Cancer (LC) is a major cancer killer worldwide, and 5-yr survival is extremely poor (≤15%), accentuating the need for more effective diagnostic and therapeutic strategies. Studies have shown cell-free microRNAs (miRNAs) circulating in the serum and plasma with specific expression in cancer, indicating the potential of using miRNAs as biomarkers for cancer diagnosis and therapy. This study aimed to identify differentially-expressed two miRNAs in the plasma of Non-Small Cell Lung Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…In general, the deregulation of microRNA expression has been associated with gene alterations that are commonly linked to smoke-related cancers [67][68][69]. The "oncomirs" miR-21 and miR-155 have previously been associated with cancers of the upper aerodigestive tract [48,49,[51][52][53][54]. In particular, miR-21 has been considered as a marker of poor prognosis in lung and head and neck cancer [70,71].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the deregulation of microRNA expression has been associated with gene alterations that are commonly linked to smoke-related cancers [67][68][69]. The "oncomirs" miR-21 and miR-155 have previously been associated with cancers of the upper aerodigestive tract [48,49,[51][52][53][54]. In particular, miR-21 has been considered as a marker of poor prognosis in lung and head and neck cancer [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have also shown that oncomir miR-21 downregulates hMSH2 gene expression by targeting the 3 untranslated region of its mRNA [45], and that miR-155 can significantly downregulate hMSH2, hMSH6, and hMLH1 [46], while others have suggested that miRNAs play an important role in modulating cell cycle progression by targeting hMSH2 in lung cancer [42]. Although there are reports suggesting a relationship between the MMR mechanism and miRNA profiles [41,43,44,46], the underlying molecular mechanism by which tobacco smoke carcinogens induce miRNA deregulation and affect the expression profiles of mismatch repair genes, particularly in lung and head and neck cancer, is not yet known.Here, we attempt to explore whether NNK affects the expression of small regulatory molecules, such as known miRNA markers, previously associated with upper aerodigestive tract malignancies [47][48][49][50][51][52][53][54] that may directly or indirectly be involved in the regulation for MMR expression phenotypes. Understanding the molecular changes induced by various risk factors, such as tobacco smoke, which promote the development and progression of cancer, will help to develop new diagnostic and therapeutic approaches [55,56], leading to optimization of their management.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 26 788 deaths were reported in 2017, and the reported mortality rate was 55.65/100 000. [6][7][8][9][10] However, the functions of miRNA remain unclear. The mortality of lung cancer increases with age; the mortality rate among the elderly (>65 years) reached 299.2/100 000.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some studies reported that serum/plasma miRNA expression profile could effectively distinguish between cancer patients and healthy individuals and might be related to the development of lung cancer [3][4][5] or might have potential clinical value in the early diagnosis, prognostic, and therapeutic of lung cancer. [6][7][8][9][10] However, the functions of miRNA remain unclear. Therefore, we used a miRNA chip screening system for lung cancer, and then, real-time fluorescent quantitative PCR (RT-PCR) verification method to investigate the difference of plasma miRNA expression profile between lung cancer patients and healthy controls to predict target genes and to analyze the signal pathways, and to explore the relationship between miRNA and the genesis and the development of lung cancer.…”
Section: Introductionmentioning
confidence: 99%